Development Of English-Speaking Competencies In Primary Education - Shirinoy Yusupova (Euro Asian Journal Publishing, 2024)
In today's modern education, it is necessary to master not only language and speech, but also material related to country studies and linguistic and cultural studies. There is a need to apply socio-cultural and intercultural approaches to English language education. All this complicates the teacher's task of choosing and presenting language and speech material that is appropriate and specific to the age of the student for textbooks and working curricula.
Keywords: textbook; curriculum; speech materials; linguistic